2016
DOI: 10.3892/ol.2016.5313
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol inhibits proliferation of laryngeal squamous cell carcinoma

Abstract: Abstract. Xanthohumol is a flavonoid compound that exhibits antioxidant and anticancer effects, and is used to treat atherosclerosis. The aim of the present study was to investigate the effect of xanthohumol on the cell proliferation of laryngeal squamous cell carcinoma and to understand the mechanism of its action. The effects of xanthohumol on the cell viability and apoptosis rate of laryngeal squamous cell carcinoma SCC4 cells were assessed by Annexin V-fluorescein isothiocyanate/propidium iodide staining. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…It has been reported that Xn treatment reduced the cell viability of LSCC cells (RK33 and RK45), but had very low or no toxicity in normal cells (rat oligodendroglia-derived cells, OLN-93 and human skin fibroblasts, HSF) ( Slawinska-Brych et al, 2015 ). Moreover, Xn exhibited potent cytotoxicity in SCC4 cells, which may be associated with suppression on Mcl-1 and Bcl-2 expression, as well as PARP, p53, and AIF activation ( Li et al, 2016 ). Although changes in these protein expressions or activities have been observed upon Xn treatment, lack of knockdown or overexpression methods to further determine the molecular target of Xn in LSCC.…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…It has been reported that Xn treatment reduced the cell viability of LSCC cells (RK33 and RK45), but had very low or no toxicity in normal cells (rat oligodendroglia-derived cells, OLN-93 and human skin fibroblasts, HSF) ( Slawinska-Brych et al, 2015 ). Moreover, Xn exhibited potent cytotoxicity in SCC4 cells, which may be associated with suppression on Mcl-1 and Bcl-2 expression, as well as PARP, p53, and AIF activation ( Li et al, 2016 ). Although changes in these protein expressions or activities have been observed upon Xn treatment, lack of knockdown or overexpression methods to further determine the molecular target of Xn in LSCC.…”
Section: Head and Neck Cancersmentioning
confidence: 99%
“…Hop plant cones contain prenylated flavonoids among which XN have been shown to have cytotoxic effects and to modulate carcinogenesis [39][40]41]. Numerous studies analyzing biological activity showed that XN is antiproliferative and antitumor [42][43][44]41]. The mechanisms through which XN exerts its antitumor properties includes inhibition of alkaline phosphates and upregulation of cell cycle genes in the G0/G1 phase including p21 [40,44].…”
Section: Discussionmentioning
confidence: 99%
“…76,77 The same proapoptotic effect was observed in Ca Ski, 78 LNCaP, 79 and SCC4 cells. 80 However, XN was unable to exhibit antioxidant effects probably as a consequence of an increase in ROS as it has been described in human glioblastoma cells T98G. 75 There are few published studies about the neuroprotective capacity of XN.…”
Section: Effect Of Xanthohumol In C6 and Sh-sy5y Cellmentioning
confidence: 98%